Deskripsi Manajemen Pengelolaan Sanggar Sundaram Di Dusun Lilir, Kecamatan Gunungsari Kabupaten Lombok Barat - Sukreni, Desak Nyoman; Armayani, Ni Made Ria Taurisia; Intaran, I Made (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
This research aims to describe the management implemented in Sanggar Sundaram. Data collection methods were carried out using observation, interviews and documentation techniques. To support the analysis process, the theory used is management theory by Hanry Fayol which contains planning, organizing, coordinating and controlling. The results of this research are: In an effort to improve the development of the Sundaram Studio in Lilir Hamlet, Gunungsari District, West Lombok Regency, the studio management implements a management strategy to implement management functions which include planning, organizing, implementing and controlling all aspects of the studio's activities and programs. This is done to achieve predetermined goals.